Distribution of Meiofauna in Bathyal Sediments Influenced by the Oxygen Minimum Zone Off Costa Rica - Neira, Carlos; Ingels, Jeroen; Mendoza, Guillermo; Hernandez-Lopez, Elvira; Levin, Lisa A. (Frontiers in Marine Science, 2018)
Ocean deoxygenation has become a topic of increasing concern because of its potential impacts on marine ecosystems, including oxygen minimum zone (OMZ) expansion and subsequent benthic effects. We investigated the influence of oxygen concentration and organic matter (OM) availability on metazoan meiofauna within and below an OMZ in bathyal sediments off Costa Rica, testing the hypothesis that oxygen and OM levels are reflected in meiofaunal community structures and distribution. Mean total densities in our sampling cores (400-1800 m water depth) were highest with 3688 ind. 10 cm-2 at the OMZ core at 400 m water depth, decreasing rapidly downslope. Nematodes were overall dominant, with a maximum of 99.9% in the OMZ core, followed by copepods (13%), nauplii (4.8%), and polychaetes (3%). Relative copepod and nauplii abundance increased consistently with depth and increasing bottom-water O2. Meiofaunal composition was significantly different among sites, with lower taxonomic diversity at OMZ sites relative to deeper, oxygenated sites. Vertical distribution patterns within sediments showed that in strongly oxygen-depleted sites less meiofauna was concentrated in the surface sediment than at deeper slope sites. Highest meiofaunal abundance and lowest diversity occurred under lowest oxygen and highest pigment levels, whereas highest diversity occurred under highest oxygen-concentrations and low CPE, as well as high quality of sedimentary pigment (chl a/phaeo) and organic carbon (C/N). The lower meiofaunal diversity, and hence lower structural and trophic complexity, at oxygen-depleted sites raises concerns about changes in the structure and function of benthic marine ecosystems in the face of OMZ expansions.